Residential Satisfaction Of Student Housing Facilities In Malaysian Public Universities - Mohd Najib, Nurul Ulyani (2011)
Nowadays, a number of tertiary students in Malaysia were complaining about their dissatisfaction with the university-owned student housing, mostly regarding to the issues of safety, security, cleanliness, and house design aspects. Student housing is defined as a supervised shelter, built either on-campus or off-campus, to provide inexpensive lodging, and accommodate the undergraduate or postgraduate students. In a debate on how to ensure quality and successful services of student housing, residential satisfaction has been identified as the most important indicator to evaluate these criteria. This study aimed to investigate the residential satisfaction in housing facilities provided on-campus at Malaysian Research Universities (RUs). It utilised a student residential satisfaction (SRS) model to examine how satisfied students were with their living accommodation and to investigate the factors which could predict housing satisfaction and students‟ loyalty behaviours, taken into consideration the affect of physical and social variables. Simple random two-stage cluster sampling method was adopted to select the respondents and the survey was conducted face-to-face. The data were analysed using descriptive statistics, logistic regression, T-test, and One-way ANOVA. The results show that generally RUs students were satisfied with their student housing facilities with the SRS Index of 2.96 or 74% of satisfaction level. The students tended to execute positive loyalty behaviours (longer staying, retention, and recommendation). Study-bedroom, television room, meeting room and support services were revealed to strongly influence the student residential satisfaction. Moreover, different students‟ socio-physical backgrounds were found to influence difference satisfactions level perceived in student housing facilities. The results imply the importance of quality in student housing facilities as an effective medium to attract more local and international students to enrol in Malaysian universities.